The Economic Limit and Economic Burden of an Internally Held National Debt - Wright, David McC. (Quarterly Journal of Economics, 1940)
Nature of the problem, 116. — The fiscal and institutional limits: avoidance of price inflation, 117; statutory provisions, 118. — The immediate real burden, 119. — The financial burden, 119. — Tax friction, 120. — Government spending and the growth of national money income, 121. — The case where government spending and deficit financing merely offset hoarding: "dead weight" spending, 123; spending for public works, 126. — Increasing difficulty in making the necessary injection, 128. — Conclusions, 129.